Efficient photocatalytic activity of ZnO/GO/CuO nanocomposite with solar light for reduction of hexavalent chromium - Seyedeh Marzeyeh Hosseini; Saeid Asadpour; Mohsen Ghasemi; Mahboube Shirani (Scientific Reports)
Abstract This study investigates the application of ZnO/GO/CuO nanocomposite to reduce Cr(VI) under visible light in the presence of citric acid The photogenerated electrons could easily be transferred from GO to ZnO/CuO species via interfacial charge transfer in the presence of metal oxides and graphene oxide. UV–vis diffuse reflectance spectroscopy showed that charge carriers were formed in response to visible light absorption. The effect of different operating parameters, including photocatalyst dose, pH, and initial Cr(VI) concentration, was systematically evaluated during the photocatalytic process. The ZnO/GO/CuO nanocomposite exhibited a 97% reduction in hexavalent chromium (10 ppm) within 40 min at pH 5, resulting in greater efficiency than the pristine ZnO/CuO (65%), and ZnO (7%) materials. The ZnO/GO/CuO nanocomposite displayed excellent stability over six cycles, highlighting its potential for practical applications. The synthesized photocatalyst was characterized using XRD, FTIR spectroscopy, SEM, and EDX. Tert-butyl alcohol, hydroquinone, sodium oxalate, acetone, and EDTA were investigated as scavengers in reducing Cr(VI) to Cr(III). In the presence of tert-butyl alcohol, 74% chromium reduction was observed, while with other compounds, the chromium reduction rate was 99%. Finally, the result shows that ZnO/GO/CuO nanocomposite is an efficient semiconductor with a better visible light response and a smaller band edge (2.48 eV) than ZnO (3.2 eV) and ZnO/CuO (2.65 eV) can be effectively used to reduce metal pollutants.